- -

Solved Examples
Click on a 'View Solution' below for other questions:
 e   Evaluate: limz→∞ [7+12cos 2z48z+7]   e View Solution
 e   Evaluate: limt→0 (22t cos (94t))   e View Solution
 e   Evaluate: limw→∞ (12sin 9w + 39w3w)   e View Solution
 e   Evaluate: limr→∞ (5cos20 4r+34+9r)   e View Solution
 e   Evaluate: limz→0 (8z2 sin (178z) + 43 )   e View Solution
 e   For all r ∈ [- 1, 1], r4+7 ≤ f (r) ≤3r4+7. Find limr→0(f (r) + 15)   e View Solution
 e   Evaluate: lims→∞ [5sin10 5s+10s+365s+6]   e View Solution
 e   Evaluate: limq→0 (10q(sin8q + cos8q)+13)   e View Solution
 e   Evaluate: limu→- ∞ [u2(6cos 4u+10cos9 4u)(u2+8)(u-6)]   e View Solution
 e   Evaluate: limx→0(3x4(9sin8x2 - 12 cos8x2)+10)   e View Solution
 e   Evaluate: lims→0 (7s2 sin3s cos3s + 14)   e View Solution
 e   Evaluate: limu→∞(12sin (12u) + 16cos (12u)20u2)   e View Solution
 e   If 8cos x + 40 ≤ f (x) ≤ 48 + x4 for all x ∈ [- 1,1], then find limx→0 1f (x) by assuming that it exists.   e View Solution
 e   Evaluate: limk→∞ [7cos 14k10k8]   e View Solution
 e   Evaluate: limp→∞ [6sin (14p)11p10]   e View Solution
 e   Evaluate: limv→∞ (8sin 13v17v6)   e View Solution
 e   Evaluate: limv→∞ 8v4-sin 8v+1010v4+8   e View Solution
 e   If 5sin (u12)+107 ≤ h(u) ≤ 5sin (u4)+107 for all u ∈ [- 1, 1] and limu→0 h(u) exists, then find limu→0 h(u).   e View Solution
 e   If 2cos (q10)+107 ≤ g(q) ≤ 2cos (q30)+107 for all q ∈ [- 1, 1], then evaluate limq→0 g(q) by assuming that it exists.   e View Solution
 e   If 8sin 11u + 13 ≤ g(u) ≤ 21 , then find limu→π2 g(u) by assuming that it exists.   e View Solution
 e   3m4+66 ≤ f (m) ≤ 3m2+66 , where m ∈[- 1, 1] and limm→0 f (m) exists. Evaluate limm→0 f (m).   e View Solution
 e   If 7sin16p+ 246 ≤ g(p) ≤7sin10p + 246 for all p ∈ [- 1, 1], then evaluate limp→0 g(p) by assuming that it exists.   e View Solution
 e   Evaluate: limk→∞ 9cos (16k)11k2   e View Solution
 e   If 4+49v4 ≤ h(v) ≤4+49v2 for all v ∈ [- 1, 1], then evaluate limv→0 h(v).   e View Solution
 e   If 8cos8w+357 ≤ h(w) ≤8cos4w + 357 for all w ∈ [- 1, 1], then evaluate limw→0h(w).   e View Solution